Konstruksi Model Motivasi Kerja Islami: Pendekatan Tafsir Maudhu'i dan Analisis Komparatif dengan Teori Motivasi Barat: Indonesia - Erissa Putri, Ratih (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2026)
Work motivation in contemporary Muslim communities presents a complex paradox, where religious value orientations often conflict with the utilitarian logic dominating modern management theory. Existing Islamic management literature remains normative-prescriptive without producing solid and empirically testable theoretical constructs. This theoretical gap demonstrates an urgent need for a work motivation model directly derived from primary Islamic sources with practical relevance in modern organizational contexts. This study aims to develop an Islamic Work Motivation Model (IWMM) through methodological integration of al-tafsir al-maudhu'i (thematic exegesis) with systematic literature review, and to identify conceptual convergences and divergences with Western motivation theories. This research adopts a systematic literature review design integrated with the al-tafsir al-maudhu'i method. The codification process yielded 37 Qur'anic verses and 42 authentic hadiths analyzed through four stages: textual codification, thematic analysis using Braun and Clarke's framework, comparative analysis with Western motivation theories, and theoretical synthesis. The analysis identified three main categories of Islamic work motivation: (1) work as a response to divine calling rooted in muraqabah consciousness and tahqiq al-khilafah; (2) work as manifestation of trust and ihsan encompassing pillars of self-reliance ('iffah), professionalism (ihsan), and long-term commitment (istiqamah); and (3) blessed life rhythm as a temporal dimension integrating sacred time and profane time. Comparison with Self-Determination Theory, Herzberg's Two-Factor Theory, and Maslow's Hierarchy of Needs demonstrates that IWMM offers significant conceptual expansion through the addition of spiritual transcendence dimension, ihsan as meta-motivator, and reorientation from self-actualization toward taqarrub ilallah. The Islamic Work Motivation Model constructed through this research not only offers a theoretical framework with theological depth and methodological precision, but also provides a paradigmatic alternative that simultaneously integrates psychological, social, and spiritual dimensions. This model has practical implications for human resource practitioners, policymakers, and Islamic organizational leaders in building authentic and sustainable work culture.